Individual Behavior Of Female Sumatran Orangutan (Pongo abelii L.) With Enclosure Management System In Siantar Zoo - John, Arlen Hanel (International Journal of Ecophysiology, 2022)
Sumatran orangutans (Pongoabelii L.) is an endangered species due to habitat destruction. Conservation strategies need to be done in preventing extinction of orangutans, such as ex-situ conservation in Siantar zoo. This study aims to determine the behavior of individual male orangutan at Siantar Zoo with a management system. The observatuons was conducted for 14 days in August with the Focal Animal Sampling method, data recorded using the Instantaneous method and descriptive data using the Open Ended interview technique. The results showed the overall frequency of individual male orangutan behavior were locomotion (33,43%), resting (27,36%), eating (25,24%), playing (9%), agonistic (3,64%), self care (0,83%) and pooping (0,5%). The behavior of individual male orangutan is influenced by the number of visitors, namely the locomotion behavior of the crowded visitor category (34,37%), medium (30,31%) and quiet (33,18%). The resting behavior of crowded visitor catego ry (25,02%), medium (28,19%) and quiet (27,44%). The eating behavior for crowded, medium and quiet categories was 25,96% ; 25,47% and 26,30%. The playing behavior in crowded, medium and quiet categories is 7,96% ; 7,71% ; 9,75%. Agonistic behavior in crowded categories (5,44%), medium (7,11%) and quiet ( 1,96%). Self-care behavior for crowded,medium and quiet categories was 0,64% ; 0,83% ; 0,88%. The pooping behavior in the crowded category is 0,59%, in the medium category is 0,38% and in the quiet category is 0,49%. Themanagement system for male orangutan at Siantar Zoo already has a fairly good and regular system. The cage management has met the minimum requirements and the male orangutan has a optimal body weight and has never been infected with a serious disease.